Integrating Science and Art of Medicine - Nadeem Ikram, Nadeem Ikram (Journal of Rawalpindi Medical College, 2019)
The art of medicine and science of medicine are not antagonistic but supplementary to each other. There are both important differences and similarities between science and arts . Art rediscovers , generation after generation , what is necessary to humanness . Basic elements of art, according to Aristotle , are symmetry, proportion and an organic order of parts in united whole. True art is moral. It seeks to improve life and not to debase it. Even artistic modes needs scientific evaluation .Art does not mean wandering in the wilderness. By enlarge medical professionals try to use and construct all these artistic needs in the human body and soul. It is naïve to say that art does badly what science does well, or the contrary. Illness, disease, and medical context provide the mixture of emotion, drama, irony, humour, blood and gore which is grist to the mill of the novel, play, film and a TV serial. Medicine and art have a common goal to complete what nature cannot bring to a finish, i.e., to reach the ideal, to heal creation. This is done by paying attention. Physician attends the patient, artist attends the nature. Art like medicine is not an arrival. It’s a search. That is why medicine by itself is called an art. Being a doctor, considered as a species of logic and rationality, need not to be frightened by the art, as if it is some thing superfluous. Oscar Wilde said very rightly “Life imitates art far more than the art imitates life”